Initial reaction mechanism between HO· and bisphenol‐F: Conformational dependence and the role of nonbond interactions. Issue 6 (15th March 2017) - Bian, Cheng; Li, Yu; Wang, Shujuan; Jing, Xinli
Abstract: Hydroxyl radical (HO·) plays an important role in the initial pyrolysis of hydroxyl‐containing polymers, such as phenolic resin (PR). In this study, the reaction mechanism between HO· and bisphenol‐F (BPF) or tetra‐methyl substituted BPFs, which were taken as the model molecules of PR, was studied with the density functional theory approach. The results based on the Fukui function and reduced density gradient function showed that, both the hydroxyls and the carbon atoms in the phenolic groups are the reactive sites for HO· attack. The hydroxyls are most likely to be attacked by HO· owing to the strong electrostatic potential around the hydroxyls and the low reaction barriers, especially for cis‐ o ‐ o ' type BPF. The strong p —π (CH—π and OH—π) interaction between the phenolic rings in BPF leads to decreased conjugative effect of the phenolic rings, which further lead to decreased addition barriers and reaction rate constant. Abstract : Bisphenol‐Fs (BPFs) are the raw materials of epoxy and phenolic resins. A detailed investigation on the reactions between radical HO· and BPFs, which play a role of the initial pyrolysis of BPFs, is conducive to guiding the design of new such compounds. Over 80 addition and hydrogen‐abstraction paths could be computationally verified for the reactions of "HO· + BPFs." The conformational isomerism and the intramolecular interactions of BPFs determine the primary products distribution.